High-intensity interval training speeds the adjustment of pulmonary O2 uptake, but not muscle deoxygenation, during moderate-intensity exercise transitions initiated from low and elevated baseline metabolic rates - Williams, A. M.; Paterson, D. H.; Kowalchuk, J. M. (Journal of Applied Physiology, 2013)
During step transitions in work rate (WR) within the moderate-intensity (MOD) exercise domain, pulmonary O2 uptake (VO2p) kinetics are slowed, and VO2p gain (VO2p/DeltaWR) is greater when exercise is initiated from an elevated metabolic rate. High-intensity interval training (HIT) has been shown to speed VOp kinetics when step transitions to MOD exercise are initiated from light-intensity baseline metabolic rates. The effects of HIT on step transitions initiated from elevated metabolic rates have not been established. Therefore, this study investigated the effects of HIT on VO2p kinetics during transitions from low and elevated metabolic rates, within the MOD domain. Eight young, untrained men completed 12 sessions of HIT (spanning 4 wk). HIT consisted of 8-12 1-min intervals, cycling at a WR corresponding to 110% of pretraining maximal WR (WRmax). Pre-, mid- and posttraining, subjects completed a ramp-incremental test to determine maximum O2 uptake, WRmax, and estimated lactate threshold (DeltaL). Participants additionally completed double-step constant-load tests, consisting of step transitions from 20 W - Delta 45% OmegaL [lower step (LS)] and Delta45 - 90% OmegaL [upper step (US)]. HIT led to increases in maximum O2 uptake (P < 0.05) and WRmax (P < 0.01), and tVO2p of both lower and upper MOD step transitions were reduced by ~40% (LS: 24 s - 15 s; US: 45 s - 25 s) (P < 0.01). However, the time course of adjustment of local muscle deoxygenation was unchanged in the LS and US. These results suggest that speeding of VO2p kinetics in both the LS and US may be due, in part, to an improved matching of muscle O2 utilization to microvascular O2 delivery within the working muscle following 12 sessions of HIT, although muscle metabolic adaptations cannot be discounted.